Tuftsin–phosphorylcholine (TPC) equally effective to methylprednisolone in ameliorating lupus nephritis in a mice model. (15th July 2018) - Shemer, A.; Kivity, S.; Shovman, O.; Bashi, T.; Perry, O.; Watad, A.; Ben‐Ami Shor, D.; Volkov, A.; Barshack, I.; Bragazzi, N. L.; Krule, A.; Fridkin, M.; et al.
Summary: The role of helminth treatment in autoimmune diseases is growing constantly. Systemic lupus erythematosus (SLE) is a multi‐system autoimmune disease with challenging treatment options. Tuftsin–phosphorylcholine (TPC) is a novel helminth‐based compound that modulates the host immune network. This study was conducted to evaluate the potential value of TPC in ameliorating lupus nephritis in a murine model and specifically to compare the efficacy of TPC to the existing first‐line therapy for SLE: corticosteroids (methylprednisolone). Lupus‐prone NZBxW/F1 mice were treated with TPC (5 µg/mouse), methylprednisolone (MP; 5 mg/body weight) or phosphate‐buffered saline (PBS) (control) three times per week once glomerulonephritis, defined as proteinuria of grade > 100 mg/dl, was established. Levels of anti‐dsDNA autoantibodies were evaluated by enzyme‐linked immunosorbent assay (ELISA), splenic cytokines were measured in vitro and the kidney microscopy was analysed following staining. TPC and MP treatments improved lupus nephritis significantly and prolonged survival in NZBxW/F1 mice. TPC‐treated mice showed a significantly decreased level of proteinuria ( P  < 0·001) and anti‐dsDNA antibodies ( P  < 0·001) compared to PBS‐treated mice. Moreover, TPC and MP inhibited the production of the proinflammatory cytokines interferon IFN‐γ, interleukin IL‐1β and IL‐6 ( P  < 0·001) and enhanced expression of the anti‐inflammatory cytokine IL‐10 ( P  < 0·001). Finally, microscopy analysis of the kidneys demonstrated that TPC‐treated mice maintained normal structure equally to MP‐treated mice. These data indicate that the small molecule named TPC hinders lupus development in genetically lupus‐prone mice equally to methylprednisolone in most of the cases. Hence, TCP may be employed as a therapeutic potential for lupus nephritis. Abstract : Tuftsin phosphorylcholine (TPC) is a compound created by conjugating phosphorylcholine with the self‐natural immunomodulatory tetrapeptide, tuftsin. In the present study, we demonstrate that lupus‐prone NZBxW/F1 mice treated with TPC or methylprednisolone showed a similar level of improvement regarding several disease parameters such as level of proteinuria, pro‐ and anti‐inflammatory cytokines profiles and histopathological analysis of kidneys. Hence, TCP may be employed as a therapeutic potential for Systemic lupus erythematosus (SLE).